Significance of Probiotics as Feed Additives in Livestock and Poultry Nutr - Kumar, Sachin; Tariq, Hujaz; Singh, Anukarna; Tyagi, Nitin; Mondal, Goutam; Gupta, Mahesh; Tyagi, A. K. (Indian Journal of Animal Nutrition, 2017)
A number of feed additives such as antibiotics, probiotics, oligosaccharides, enzymes and organic acids have been used in livestock feeds for improving productivity and maintaining gut eubiosis. Antibiotics have been widely used in livestock diets, however, development of antimicrobial resistance to these antibiotics urged scientists to find viable alternatives to the use of antibiotics that could enhance the productivity as well as natural defense mechanisms of animals. Probiotics are technically viable alternatives to antibiotics in livestock feed. Probiotics are the live culture of host-friendly microbes which upon ingestion exert health effects to the host. Probiotics have been established as a good alternative which can enhance intestinal health by stimulating the development of a healthy microbiota (predominated by beneficial bacteria), competing with pathogenic bacteria for nutrients in the gut, preventing enteric pathogens from colonizing the intestine, increasing digestive capacity and lowering the pH and altering mucosal immunity. Moreover, nutritional intervention through probiotics supplementation seems be a natural and holistic strategy to combat such challenges. The beneficial response to probiotics supplementation seems to be affected by both source and dose of probiotics supplemented in particular species. The present review is an attempt to explore the use of different probiotics in livestock feed and thetr probable mode of actions through which they exhibit their beneficial effects in animals.